2007
DOI: 10.1007/s00417-007-0723-1
|View full text |Cite
|
Sign up to set email alerts
|

Poor binocular coordination of saccades in dyslexic children

Abstract: Poor quality of binocular coordination of saccades and drift of the eyes after the saccade, regardless of the task, indicates an intrinsic ocular motor deficiency. Such a deficiency could be related to immaturity of the normal ocular motor learning mechanisms via which ocular motor coordination and stable fixation are achieved. Learning could be based on the interaction between the saccade and vergence subsystems. The cerebellum, but also cortical areas of the magnocellular stream such as the parietal cortex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
104
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 32 publications
20
104
1
1
Order By: Relevance
“…Indeed, the fact that dyslexic children are able to improve antisaccade performance with training as shown by Fischer and Hartnegg (2000b) is in line with the hypothesis of a delayed maturation of the oculomotor system in such type of subjects (Bucci et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
“…Indeed, the fact that dyslexic children are able to improve antisaccade performance with training as shown by Fischer and Hartnegg (2000b) is in line with the hypothesis of a delayed maturation of the oculomotor system in such type of subjects (Bucci et al, 2008).…”
Section: Introductionsupporting
confidence: 69%
“…The population with learning disorders examined by these authors was not wellcharacterized (no refractive and phorometric data were mentioned) and there are many unclear methodological procedures. Using a photoelectric system to assess saccadic eye movements, Bucci et al [3] detected poor binocular coordination during and after saccades in dyslexic compared to non-dyslexic children.…”
Section: Discussionmentioning
confidence: 99%
“…Saccadic eye movements have frequently been related to reading ability in several primary school grades [5,6]. Recently Bucci et al [3] found that in a word-reading task the total fixation period is significantly longer in dyslexics than in non-dyslexic children; and the coordination of saccades is poor in a dyslexic child compared to a non-dyslexic child. Stein and Fowler et al [7] and Eden et al [8] reported a reduced ability in dyslexics to maintain steady fixation during prolonged (5-s) viewing of the target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such difficulties might imply weak connections between different language components, and consequently result in slower speed processing regardless of mapping consistency between spelling and sound (Paulesu et al, 2001;Ziegler, 2006). Impaired phonological awareness, that is, incorrect use of knowledge about letter-sound correspondences, and unsuccessful retrieval of phonological representations may be essential factors that can affect the reading process (Bruck, 1992;Ramus, 2001b;Ramus & Szenkovits, 2008;Vellutino, Scanlon, & Spearing, 1995;Wagner & Torgesen, 1987;Wimmer, 1996), but cannot exclusively account for the most frequently reported dyslexia deficits in reading, such as, shorter saccades and hence more fixations, longer fixation durations, more regressions, poor tracking from left to right, as well as poor binocular convergence (e.g., Bucci, Brémond-Gignac, & Kapoula, 2008;Morris & Rayner, 1991;Rayner, 1998;Snowling, 2000;Stein & Walsh, 1997).…”
Section: Effects Of Dyslexia In Transparent Orthographiesmentioning
confidence: 97%